MSMEs PRODUCT SELLING PRICING STRATEGY TO INCREASE PROFITS USING THE COST PLUS PRICING APPROACH - Anissa Tifanny Pratista; Rudi Santoso (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to examine and implement a strategy for determining the cost of production using cost plus pricing. The basic assumption of this research is that there are several MSMEs that still use conventional methods to determine the cost of production. The implication is that MSMEs have the potential to lose profits because the prices set are still far from actual profits. The application of the cost-plus pricing method in MSMEs can not only increase profit potential but also be used to promote products with price discounts. The research results show that there is a 640% increase in profits when MSMEs apply the cost-plus pricing method. In addition, at certain moments, MSMEs can provide discounts of up to 20% without losing profits. The limitation of this research lies in the scale of the object which is still small. Thus, this research cannot be generalized to be applied to different objects. However, this research provides recommendations for further research with larger objects, so that the differences can be seen.